Quasi (s,r)-Contractive Multi-Valued Operators on b-Metric Space and Related Fixed Point Theorems - Ei Ei Nyein; Aung Khaing Zaw (Journal of the Indonesian Mathematical Society, 2020)
This paper aims to introduce a new type of quasi (s,r)-contractive multi-valued operator on b-complete metric space and to extend the results for the fixed point theorems of quasi (s,r)-contractive multi-valued operator. As an application, the  existence of the solution for a type of differential equation is given.